Analisis Inovasi Bank Sampah Dalam Pengelolaan Sampah Rumah Tangga Perkotaan Di Kelurahan Bahagia Kecamatan Babelan Kabupaten Bekasi - Hartono Hartono; Suprapti Widiasih; Mary Ismowati (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
The purpose of this research is to analyze and evaluate waste bank innovation in urban household waste management in Bahagia Village, Babelan Sub-district, Bekasi Regency. This research is a qualitative descriptive research, a research aiming to describe a phenomena. Data is collected thorough interview, observation, and documentation. Data validity is tested by using triangulation. Data is analyzed in a descriptive-qualitative way by using narration.  Referring to Sebastian (2014: 37) on three types of innovation (product, process, and quality innovation), the result shows that: 1) the waste bank innovation has been well directed and implemented, 2) the obstacles are the lack of capital for operational, the community’s lack of understanding on the household waste management core problem, and not everyone is aware to do the waste management and processing, using limited time, place, and scavenger mindset as excuses. The three efforts are: 1) PBSB invitation to more environmental CSRs, 2) continuous socialization to make the community understand more about eco-friendly waste management, and 3) innovation breakthroughs on waste management. It is suggested that modules on making compost and biopore should be made as community guide and that waste bank 3R campaign can be financially supported by the government.